Tragiški užitki v Aristotelovi Poetiki - Marušič, Jera (Keria (Ljubljana), 2000)
Our notion of the pleasure provided by tragedy has undoubtedly its origin in Aristotle's Poetics: we indeed associate this pleasure with pity and fears as well as with catharsis, notions that are all derived from this treatise. On the other hand, we find it difficult to explain why this pleasure takes place at all: we experience it while wittnessing most horrible scenes, represented in tragedy, scenes that would arouse only great pain in us, if they were real. Does Aristotle's discussion of tragedy and of "the pleasure from pity and fear" help us to explain the paradoxical nature of this pleasure? In the article I search for Aristotle's answer as to why tragedy provides pleasure.
Keywords: Aristoteles; Aristoteles: Poetika; grška filozofija; grška tragedija; užitek